Um estudo sobre a formação linguística dos instrutores de Libras em Palmas - Tocantins - Bueres, Teresa Cristina Hitomi Kikuchi (2010)
This research was developed in purpose to discover that the difficulties that lead instructors of deaf in Palmas Tocantins to get a low grade in the National exam of proficiency in LIBRAS. For view of the problem of the high failure rate of the deaf tocantinense in the PROLIBRAS program. For this, we need to investigate the languager training of deaf educators to teaching Brazilian Sign language, provided L1, in Palmas - Tocantins. Data collect on deaf instructors in the state capital to identify the weaknesses of LIBRAS language of this professionals in the city. The data was collected through filming interview semistructured group, literature review and questionnaire. Data analysis followed the sociolinguistic line therefore raised the hypothesis that deaf people in Tocantins have spoken a language variant of LIBRAS a close variant to portuguese signaled modality that matches portuguese language with sign language, and thus there was the discovery of the existence of a lingistic isolation of the deaf community of Tocantins, causing many difficulties in the signs interpretation shown during the examination of PROLIBRAS. In the end it was realized the need to graduate in higher level in letters/LIBRAS to deaf instructors. It is understood as essential to overcome the common sense view and develop knowledge applied to teaching LIBRAS in Palmas-TO.